2020
DOI: 10.1021/acsami.0c06417
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Organic Framework Nanosheets as Reactive Fillers To Fabricate Free-Standing Polyamide Membranes for Efficient Desalination

Abstract: Mixed matrix membranes (MMMs) have been increasingly utilized in membrane processes. Covalent organic frameworks (COFs) hold great promise as emergent nanofillers to fabricate high-performance MMMs; however, only few studies about COF materials in MMMs have been reported where COFs are all used as nonreactive fillers. Herein, we propose using −NH2-functionalized COF nanosheets as reactive fillers (rCON) to fabricate MMMs. rCON altered the morphology and chemistry of MMMs by controlling the diffusion rate of pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(28 citation statements)
references
References 57 publications
1
23
0
1
Order By: Relevance
“…Meanwhile, Jiang and coworkers demonstrated that the rCON obtained by chemical exfoliation of covalent triazine-based framework-1 (CTF-1) (a triazine-based COF) could serve as a filler to fabricate free-standing COF-based TFN membrane for desalination. [140] Because the enhanced interactions that occur between rCON and PIP as a result of hydrogen bonding slow down the diffusion rate of monomers during the IP process, the effective filtration area of the obtained membranes is increased accompanying with the formation of wrinkles. As a result, the as-synthesized membranes exhibited an outstanding desalination performance.…”
Section: Blendingmentioning
confidence: 99%
“…Meanwhile, Jiang and coworkers demonstrated that the rCON obtained by chemical exfoliation of covalent triazine-based framework-1 (CTF-1) (a triazine-based COF) could serve as a filler to fabricate free-standing COF-based TFN membrane for desalination. [140] Because the enhanced interactions that occur between rCON and PIP as a result of hydrogen bonding slow down the diffusion rate of monomers during the IP process, the effective filtration area of the obtained membranes is increased accompanying with the formation of wrinkles. As a result, the as-synthesized membranes exhibited an outstanding desalination performance.…”
Section: Blendingmentioning
confidence: 99%
“…In addition, the size and characteristics of nanosheets might be altered due to the spraying effect. Alternative options such as support-free IP technique, 134 reverse IP technique, 135,136 stitching of nanosheets prior to IP reactions 100 and nanosheets interlayer 43 from difficulties to attach or transfer the fabricated fragile PA layer onto the support membrane. Reverse IP is similar to the conventional IP technique with the sequence of contacting the aqueous and organic phase reversed.…”
Section: Challenges In Manufacturing In Designmentioning
confidence: 99%
“…Later on, in a similar study, these authors reported the preparation of TFN membranes through COF nanosheets, which showed good performance in water desalination [ 44 ]. Once again, the presence of amino and hydroxyl groups in the COF nanosheets favored formatting hydrogen bonds between them and PIP in the aqueous solution, which decreased the diffusion rates and consequently improved the quality of the membrane as well as its hydrophilicity.…”
Section: Cof Processingmentioning
confidence: 99%
“…Recently, the same group [ 44 ] reported for the first time a MMM for desalination based on reactive fillers. For that, they made use of reactive CONs (rCONs) of the COF CTF-1, which acted as filler of PA.…”
Section: Cofs For Water Treatmentmentioning
confidence: 99%
See 1 more Smart Citation